2021
DOI: 10.7759/cureus.18087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Port-Site Pain After Gallbladder Retrieval From Epigastric Versus Umbilical Port in Patients of Laparoscopic Cholecystectomy for Symptomatic Cholelithiasis: A Randomized Controlled Trial

Abstract: IntroductionGallbladder (GB) retrieval is an important cause of postoperative pain (POP) after laparoscopic cholecystectomy (LC). Retrieval is through the epigastric or umbilical port based on the surgeon's preference. There is limited evidence to support the superiority of one port over the other in terms of POP. This study was done to compare POP between epigastric and umbilical ports after GB retrieval in LC for symptomatic cholelithiasis. Material and methodsAll patients who underwent elective LC for sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Consistent with other randomized trials [8,11,12], our study showed a higher incidence of port site infections in the epigastric group. The umbilical port is usually visualized as a "dirty" port, considering its ignorance during bathing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with other randomized trials [8,11,12], our study showed a higher incidence of port site infections in the epigastric group. The umbilical port is usually visualized as a "dirty" port, considering its ignorance during bathing.…”
Section: Discussionsupporting
confidence: 92%
“…The only study that we could find that reported the methods of sample size calculation was by Siddique et al [5] and Jain et al [11]. Our sample size was calculated considering it to be a superiority trial, as previous studies reported mixed results, most favouring umbilical port sites and a few favouring epigastric port sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations